2015
DOI: 10.1021/acs.organomet.5b00556
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of the Lewis Acidity of Silylium Ions

Abstract: The Lewis acidity of several aryl-substituted tetrylium ions was classified experimentally by applying the Gutmann−Beckett method and computationally by calculation of fluoride ion affinities (FIA) (tetrel elements = Si, Ge). According to these measures, tetrylium ions are significantly more Lewis acidic than boranes, and aryl-substituted silylium borates are among the strongest isolable Lewis acids. A finetuning of the Lewis acidity of silylium ions is possible by taking advantage of electronic and/or steric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 47 publications
7
79
0
5
Order By: Relevance
“…Moreover, these desirable properties of aluminate salts have been exploited in an umber of applications.I na ddition, as eries of related borates [B(OR) 4 ] À (where R = C(H)(CF 3 ) 2 (OR HF ) and CH 2 CF 3 (tfe)) have also been published and investigated as WCAsf or ionic liquids.T hese borates typically demonstrate higher melting points and viscosities than their aluminate counterparts,t hus making them more applicable for battery electrolytes than ionic liquids. [132] Equally important in the application of aluminate WCAsisthe facile conversion of the lithium salts into anumber of other starting materials of synthetic importance through multigram meta- [6,7,[133][134][135] Of particular note is the ready formation of the donor-free Ag[Al(OR F ) 4 ]s alt, as tarting material not available with many WCA classes (Scheme 1). Themeasured ionicities of the [Al(OR HF ) 4 ] À ion in aseries of ionic liquids has been shown to reach 100 %, and to always be greater than those of the [NTf 2 ] À salt with the same cation.…”
Section: Aluminate Anionsmentioning
confidence: 99%
“…Moreover, these desirable properties of aluminate salts have been exploited in an umber of applications.I na ddition, as eries of related borates [B(OR) 4 ] À (where R = C(H)(CF 3 ) 2 (OR HF ) and CH 2 CF 3 (tfe)) have also been published and investigated as WCAsf or ionic liquids.T hese borates typically demonstrate higher melting points and viscosities than their aluminate counterparts,t hus making them more applicable for battery electrolytes than ionic liquids. [132] Equally important in the application of aluminate WCAsisthe facile conversion of the lithium salts into anumber of other starting materials of synthetic importance through multigram meta- [6,7,[133][134][135] Of particular note is the ready formation of the donor-free Ag[Al(OR F ) 4 ]s alt, as tarting material not available with many WCA classes (Scheme 1). Themeasured ionicities of the [Al(OR HF ) 4 ] À ion in aseries of ionic liquids has been shown to reach 100 %, and to always be greater than those of the [NTf 2 ] À salt with the same cation.…”
Section: Aluminate Anionsmentioning
confidence: 99%
“…Related to these methods, Hilt and co‐workers applied the 2 H NMR chemical shifts of the γ‐deuterium of the Lewis acid complexes of perdeutero‐pyridine to gauge their acidity . Although Childs method could not be applied to cationic silyl Lewis acids, pyridine as well as phosphane oxides have been used to measure their Lewis acidity and these investigations revealed the high Lewis acidity of cationic silicon compounds . In addition, it was shown that these methods fail to gauge correctly the Lewis acidity of intramolecularly stabilized silyl cations I .…”
Section: Introductionmentioning
confidence: 99%
“…The [Al(OR F ) 4 ] – WCA also shows excellent stability towards Brønsted acids, it is stable up to the level of protonated mesitylene, and towards the electrophilic cations [CX 3 ] + (X = Cl, Br or I) and the bulky silylium ion [Si(C 6 Me 5 ) 3 ] + . However, in the presence of smaller extreme electrophiles, such as in‐situ generated “[PCl 2 ] + ” {from Ag[Al(OR F ) 4 ] and PCl 3 }, or smaller alkyl silylium ions [R 3 Si] + , decomposition of the anion occurs.…”
Section: Introductionmentioning
confidence: 99%